Multicultural Education in the perspective of the Qur'an and Hadith: Concepts and Implementation: Pendidikan Multikultural dalam perspektif Al-Qur’an dan Hadis: Konsep dan Implementasi - Gozali, Ahd (Universitas Muhammadiyah Sidoarjo, 2024)
Multicultural education is education that accommodates cultural and societal diversity. In the perspective of the Qur'an and Hadith, multicultural education is considered important for developing awareness of diversity and tolerance towards differences. This research aims to analyze multicultural education in the perspective of the Qur'an and Hadith. The method used in this research is a qualitative method with a literature study approach using hermeneutic approach. The data used in this research are the Qur'an, tafsir books, and hadiths from Kutub as-Sittah. The data obtained were analyzed using content analysis techniques. The results of the research show that the Qur'an and Hadith provide strong support for multicultural education by providing clear concepts such as Tolerance, Justice, Democracy, Equality, as well as Brotherhood and kinship.